Lexical Cohesion in Shereen Salama’s Speech - Eka Indah Nuraini; Melani Nathania; Nur Afifah (LPPM Universitas Bina Sarana Informatika, 2024)
The purpose of this article is to analyze the types of lexical cohesion found in an English speech presented by Shereen Salama on English Speeches YouTube channel. The 13-minute-long video contained motivational words for Muslim youth without any political purposes. The video then was transcribed and analyzed using a descriptive qualitative method in the form of content analysis. The gathered data eventually were classified based on Haliday dan Hasan’ theory. The result findings showed that there were 26 synonyms, 1 superordinate, 1 collocation, and 57 repetition data. The most frequent lexical cohesion type was repetition words which appeared as many as 57 times. Key words: lexical cohesion, speech, types